Third Degree Haemorrhoidal-Prolapse: A Case Presented To Emergency Department - Asma Niaz Khan (ziauddin University, 2024)
Anatomically, the veins present in the rectal submucous layer are organised as internal and external haemorrhoidal plexus. Haemorrhoids develop due to abnormal varicose dilatations of the venous plexus in the rectal submucous layer. Haemorrhoidal disease is a common anorectal condition affecting 4% of the adult population. As far as prevalence is concerned, data is not easily available. Underreporting is very common and large numbers of cases are asymptomatic. A 72years old male patient presented to emergency department with severe pain and per rectal bleeding due to third degree prolapsed haemorrhoids. He had co-morbidity of hypertension, diabetes and was asthmatic. His blood pressure was 180/96mmhg and blood random sugar was 330mg/dl, on examination of chest basal crepts were present and wheezing was also auscultated in the chest. The case was diagnosed as a complication of third degree haemorrhoid post banding attempt by an inexperienced GP. It was third or early fourth degree haemorrhoids, which was difficult to differentiate due to prolapse. The case was followed for 1 year, with no complications. Third degree haemorrhoids can be catered under local anesthesia. Key Words: Third degree haemorrhoids, haemorrhoids, rubber band ligation